Realization of Multimode OAM Beams with Almost the Same Divergence Angles - Yunfan Zhang; Xianling Liang; Weihao Qi; Hongliang Wu; Qian Chen; Junping Geng; Wei Wang (International Journal of Antennas and Propagation)
This paper proposes a new method of realizing multimode OAM beams with almost the same divergence angles. The theoretical relationship between the divergence angle of the OAM beam and its radiation source is presented, and the radiation source distributions for various mode OAM beams with the same divergence angle range are discussed. In order to verify this method, an eight-mode OAM antenna constructed by a bifocal parabolic reflector and dual OAM feeds is designed and simulated. The simulation results show that the divergence angle ranges of 3 dB beamwidth for OAM modes l=±1,±2,±3,±4 are 2.2°,4.6°,2.2°,5.0°,2.4°,4.4°, and 2.6°,4.8°, the divergence angles corresponding to the maximum beam directions are 3.5°,3.6°,3.5°, and 3.8°, respectively, and the maximum difference is within 0.3°.